2014
DOI: 10.1128/jvi.03423-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel DDB2-ATM Feedback Loop Regulates Human Cytomegalovirus Replication

Abstract: Human cytomegalovirus (HCMV) genome replication requires host DNA damage responses (DDRs) and raises the possibility that DNA repair pathways may influence viral replication. We report here that a nucleotide excision repair (NER)-associatedfactor is required for efficient HCMV DNA replication. Mutations in genes encoding NER factors are associated with xeroderma pigmentosum (XP). One of the XP complementation groups, XPE, involves mutation in ddb2, which encodes DNA damage binding protein 2 (DDB2). Infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 80 publications
(106 reference statements)
1
9
0
Order By: Relevance
“…This in turn results in activation of IκB kinase (IKK), degradation of IKBA, and activation of NF-kB. Previous studies have shown that ATM signaling is required for efficient HCMV replication, and knockdown of ATM resulted in a similar phenotype as knockdown of ERC1 in our screen, supporting a role for ERC1 in proviral DNA damage signaling during HCMV infection ( 31 ). Studies are ongoing to define whether either or both ERC1 pathways are involved in HCMV replication.…”
Section: Discussionsupporting
confidence: 81%
“…This in turn results in activation of IκB kinase (IKK), degradation of IKBA, and activation of NF-kB. Previous studies have shown that ATM signaling is required for efficient HCMV replication, and knockdown of ATM resulted in a similar phenotype as knockdown of ERC1 in our screen, supporting a role for ERC1 in proviral DNA damage signaling during HCMV infection ( 31 ). Studies are ongoing to define whether either or both ERC1 pathways are involved in HCMV replication.…”
Section: Discussionsupporting
confidence: 81%
“…5B ) in UL21a-RXL-mutant-infected cells indicate that HCMV overrides these checkpoints, most likely by abrogating p53 and Chk2-dependent signaling [85] , [86] . This and the partitioning of DNA repair enzymes to viral replication compartments predisposes the host cells to the accumulation of DNA damage [49] , [87] , [88] . It is yet unclear to what extent the intrinsic genotoxicity of HCMV contributes to the severe chromosomal instability seen after mitotic entry of infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular DNA and cell-associated viral DNA were isolated using a DNeasy Blood & Tissue Kit (Qiagen). Viral DNA ( UL83 ) and host DNA (β -ACTIN ) were quantified by real-time quantitative PCR as described (72).…”
Section: Methodsmentioning
confidence: 99%